Analisis Nilai Budaya dalam Serial Animasi Маша и Медведь (Masha and The Bear) - Huges Najma Masroora; Yusril Nurul Amri; Hani Sofia Muthmainnah; Nada Aulya Azzahra (JENTERA: Jurnal Kajian Sastra, 2024)
The forms of films themselves vary from story films, educational films, and documentaries to films easily liked by children, namely animated films. Animated films can be an effective tool for conveying education to children because of their attractive visual delivery style. This research focuses on interpreting various character behaviors in the animated series Маша и Медведь /Masha i Medved'/ 'Masha and The Bear' to explore the meaning contained therein, especially cultural values. This research uses a descriptive qualitative method of Koentjaraningrat theory analysis.   Koentjaraningrat believes that universal cultural values consist of seven elements, including language systems, knowledge systems, social systems, living equipment and technology systems, livelihood or economic systems, arts, and religious systems. The data collection technique used is observation and data documentation in the form of capturing each scene in the Masha and The Bear animation which is considered by researchers to be a cultural element. The results of this research show that there are cultural values contained in the data with details of language systems totaling five findings, knowledge systems totaling five data, systems of social organization or kinship relationships totaling one finding, living equipment, and technology systems totaling forty-seven findings, eye systems livelihood as many as four findings, religious systems as many as one finds, and art as many as three findings. AbstrakPenelitian ini berfokus pada interpretasi berbagai perilaku tokoh dalam serial animasi Маша и Медведь /Masha i Medved’/ Masha dan Si Beruang untuk menggali makna yang terkandung di dalamnya, khususnya nilai budaya. Penelitian ini menggunakan metode kualitatif deskriptif analisis teori Koentjaraningrat.  Koentjaraningrat berpendapat bahwa nilai-nilai budaya universal terdiri dari tujuh unsur, diantaranya adalah sistem bahasa, sistem pengetahuan, sistem sosial, sistem peralatan hidup dan teknologi, sistem mata pencaharian atau ekonomi, kesenian, dan sistem religi. Teknik pengumpulan data yang digunakan yaitu observasi dan dokumentasi data berupa tangkapan layartiap adegan pada animasi Mаша и Медведь /Masha i Medved’/ ‘Masha dan Si Beruang’ yang dianggap oleh peneliti sebagai unsur budaya. Hasil dari penelitian ini menunjukkan bahwa terdapat nilai budaya yang terkandung dalam data dengan rincian sistem bahasa sebanyak lima temuan, sistem pengetahuan sebanyak lima data, sistem organisasi sosial atau hubungan kekerabatan sebanyak satu temuan, sistem peralatan hidup dan teknologi sebanyak sebelas temuan, sistem mata pencaharian hidup sebanyak empat temuan, sistem religi sebanyak satu temuan, dan kesenian sebanyak tiga temuan.